Incidence and outcome of cardiac injury in patients with severe head trauma - Hasanin, Ahmed (Scand J Trauma Resusc Emerg Med, 2016)
BACKGROUND: Although cardiac injury has been reported in patients with various neurological conditions, few data report cardiac injury in patients with traumatic brain injury (TBI). The aim of this work is to report the incidence of cardiac injury in patients with TBI and its impact on patient outcome. METHODS: A prospective observational study was conducted on a cohort of 50 patients with severe TBI. Only patients with isolated severe TBI defined as Glascow coma scale (GCS) < 8 were included in the study. Acute physiology and chronic health evaluation (APACHE) II score, GCS, hemodynamic data, serum Troponin I, electrocardiogram (ECG), and echocardiographic examination, and patients’ outcome were recorded. A neurogenic cardiac injury score (NCIS) was calculated for all patients (rising troponin = 1, abnormal echocardiography = 1, hypotension = 1). Univariate and multivariate analyses for risk factors for mortality were done for all risk factors. RESULTS AND DISCUSSION: Fifty patients were included; age was 31 ± 12, APACHE II was 21 ± 5, and male patients were 45 (90 %). Troponin I was elevated in 27 (54 %) patients, abnormal echocardiography and hypotension were documented in 14 (28 %) and 16 (32 %) patients, respectively. The in-hospital mortality was 36 %. Risk factors for mortality by univariate analysis were age, GCS, APACHE II score, serum troponin level, NCIS, and hypotension. However, in multivariate analysis, the only two independent risk factors for mortality were APACHE II score (OR = 1.25, 95 % confidence interval: 1.02–1.54, P = 0.03) and NCIS score (OR = 8.38, 95 % confidence interval: 1.44–48.74, P = 0.018). CONCLUSIONS: Cardiac injury is common in patients with TBI and is associated with increased mortality. The association of high NCIS and poor outcome in these patients warrants a further larger study.